Penerapan Tuya Application Programming Interface (API) pada Sistem IoT Monitoring Suhu Ruang Server - Kurnia Bakti, Very; Sutanto, Achmad; Rizal Arfani, Mohammad (Politeknik Harapan Bersama, 2023)
Server computers generally work 24 hours and continuously. The tasks of the server, starting from running the operating system, applications, and data storage, are heavy and oversized. All electronic devices inside the server generate heat when operating. If they are not conditioned in a room with low temperatures, then the temperature of the server computer will increase and cause a decrease in the performance of the server. This study tested the temperature sensor available from the Application Programming Interface (API) feature from Tuya. Utilizing the API will facilitate the design of a system that can focus more on monitoring application development because the built system is no longer focused on complicated and risky hardware designs. The results of monitoring the server room's temperature can be monitored with sensors integrated with Tuya on a web-based page